Water Management in Rice-Wheat Cropping System in Indo-Gangetic Plains (Indian Journal of Extension Education, 2010)
The rice – wheat rotation has turned out to be a major cropping sequence covering 45 per cent of net area sown and filled the food grain coffers of the country. Between the two eastern states, the yield of rice and wheat has increased in Bihar, but the yield of wheat in the state of West Bengal has registered a negative growth. Assured availability of irrigation water and its judicious management plays a vital role in enhancing crop productivity along with the adoption of improved cultivars, and scientific soil fertility and pest management practices. Twenty districts lay in eastern India Gangetic plains and only two districts fall in Indus plain of Punjab and Haryana. The highest surface water development in Punjab (84.0%) followed by West Bengal (77.7%), Haryana (69.4%), Uttar Pradesh (59.3%), and Bihar (49.8%). The rainwater is short of meeting the water requirement of rice field, irriagrion water is applied to fulfill the demand of water. The irrigation requirement rages from 810 mm in Bihar plains to 2000 mm in Haryana. The increase of 3.33 cm deep percolation over normal bunds of 10 cm commonly maintained in the farmer’s fields. Thus, a field having 15 cm bund height effects a reduction in ground water withdrawal by 6.37 cm, and increase in deep percolation by 3.33 cm, thereby conserving a total of 10 cm water during the rice season. It also enables a more effective use of rainfall in the rice fields. In tube well command, there is considerable reduction in pumping hours resulting in saving in energy and increased life of pumping equipment.The irrigation water requirement has been observed to vary between 180 mm in Bihar plains to 360 mm in Haryana. The total water requirement for wheat has been estimated to fluctuate from 238 mm in Bihar to 400 mm in Punjab. The total water requirement of rice is estimated to vary from 1144 mm in Bihar plains to 1560 mm in Haryana. Thus, a total of 1382 mm to 1838 mm water is required for rice – wheat system at different locations in Indo-Gangetic plains. The study is an example of conjunctive and conservative management of rain and irrigation water in rice fields.